Flow characteristics and phase transition of subcritical to supercritical kerosene injections in a convergent nozzle. (15th February 2023) - Liu, Guigui; Lin, Yuzhen; Li, Jiaju; Xue, Xin; Hui, Xin; Sung, Chih-Jen; Yang, Yue
Abstract: The internal flow characteristics of near- and supercritical RP-3 aviation kerosene injected into an atmospheric pressure environment were experimentally investigated. The internal flow structure was visualized in a two-dimensional transparent convergent nozzle using shadowgraph imaging. A series of images of the RP-3 flow inside a convergent nozzle varying from subcritical to supercritical injection conditions were obtained for the first time. Under subcritical, critical, and supercritical pressures, different RP-3 flow structure transitions with decreasing injection temperature were examined. In addition, the associated phase transition was analyzed using the thermodynamic phase diagram of a 10-component RP-3 surrogate based on the adiabatic isentropic expansion hypothesis. Six distinct phase state regions governing the flow structure were identified, considering the phase transitions and density variations of the fuel injection from different regions during their respective expansion processes. The experimentally observed phase transition boundary with respect to injection conditions was further determined, which can be utilized to predict the onset of a drastic change in mass flow rate. Furthermore, the axial length between the nozzle exit and the onset location of observable phase transition was detected, which initially increases and then decreases with decreasing injection temperature. Further analysis showed that the unique evolution behaviour of the specific heat ratio during injection process has a strong effect on flow characteristics near critical point. Highlights: Visualize near- and super-critical RP-3 kerosene flows in a convergent nozzle. RP-3 injections originated from different states undergo different phase transitions. Identify observable phase transition boundary with respect to injection conditions. Reveal effect of test conditions on onset location of observable phase transition. Specific heat ratio strongly affects flow characteristics near critical point.